2013
DOI: 10.7897/2277-4343.04512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Guduchi Yoga in the Management of Vatarakta (Gouty Arthritis): A Clinical Study

Abstract: Vatarakta is one of the main articular diseases, which is characterized by severe pain, tenderness, inflammation and burning sensation in the affected joints. It is a tridoshaja vyadhi, with vata pradhanyata and rakta as main dushya. Sedentary lifestyle is one of the etiological factors of Vatarakta. The etiology and symptomatology of Gout is very much similar to that of Vatarakta. Gout is a pathological reaction of joint or periarticular tissues which results from deposition of monosodium urate monohydrate cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In ayurveda, Tinospora cordifolia (Willd.) Miers is used for Vataraktha (Gouty arthritis) (Huded et al 2013) and also its usage mentioned in Nighantu of Sri Bhavamisra for Vataraktha (Pandey & Bhavaprakasha, 2006). The plant Vitex negundo L is first described in Charaka Samhita which is an oldest and most authentic text of Ayurveda and successful analgesic activity is reported in several studies and databases (Sharma et al, 2005;Telang et al, 1999)…”
Section: Notes On Ayurvedic Usage Of Plantsmentioning
confidence: 99%
“…In ayurveda, Tinospora cordifolia (Willd.) Miers is used for Vataraktha (Gouty arthritis) (Huded et al 2013) and also its usage mentioned in Nighantu of Sri Bhavamisra for Vataraktha (Pandey & Bhavaprakasha, 2006). The plant Vitex negundo L is first described in Charaka Samhita which is an oldest and most authentic text of Ayurveda and successful analgesic activity is reported in several studies and databases (Sharma et al, 2005;Telang et al, 1999)…”
Section: Notes On Ayurvedic Usage Of Plantsmentioning
confidence: 99%
“…When C3 convertase is inhibited, pro inflammatory anaphylactic peptides are not released with the result that no inflammation is observed. In one of the study Guduchi Yoga had shown significant reduction in serum uric acid levels 23 …”
Section: Mechanism Of Action On Basis Of Preclinical Studiesmentioning
confidence: 98%
“…It is a Rasayana as mentioned in Ayurveda which speaks of its in-toto action. It has been proved to possess Anti inflammatory 17 , antioxidant 18 , anti cancerous 19 , cognition and memory enhancing 20 , aphrodisiac 21 , immunomodulatory 22 and management of vatarakta (Gouty arthritis) 23 effects.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Ayurveda mentions the utility of guduchi in Hruddourbalya-as it enhances cardiac wellness. Guduchi also provides sufficient iron and calcium in accordance with the daily requirement thus preventing conditions such as Iron deficiency anaemia, dizziness, weakness, fatigue, dyspnoea and neuropsychiatric manifestations of chronic hypocalcaemia [16][17][18][19][20][21][22][23] . The neurological manifestations are clubbed under the name of Vatavyadhis (Diseases caused due to vitiated Vata) in Ayurveda and the authors have clearly stated about the properties of Guduchi shaka which can pacify vata 3,4 and hence prevent occurrence of the Vatavyadhis.…”
Section: Preventive and Curative Potential Of Guduchi As Foodmentioning
confidence: 99%